On Love and the Canon: H.D., Robert Duncan, and “Venice-Venus” - Lara Vetter (Sillages Critiques)
Robert Duncan’s The H.D. Book offers an alternative literary history of modernism and contemporary poetry that moves H.D., Pound, Lawrence and Williams to its center, and that thus positions poets influenced by these four (including himself) as foundational to the post-WWII era. He also offers a narrative of H.D.’s career that elevates her poetry over her prose, which he sees as impure, mired in venery. For Duncan, Venice and Venus are at the heart of the problem with H.D.’s “Venetian” middle career. This paper will plumb representations of Venice and Venus in H.D.’s Trilogy and Duncan’s “The Venice Poem,” demonstrating how what H.D. termed “Venice-Venus” is central to Duncan’s notion of the modern American literary canon.